2019
DOI: 10.1111/irel.12228
|View full text |Cite
|
Sign up to set email alerts
|

Negotiating the Gender Wage Gap

Abstract: There is some evidence that gender differences exist in the propensity to negotiate and outcomes from negotiation. We examine the propensity to negotiate over pay with the employer, the wage outcomes resulting from negotiation, and the impact on the gender wage gap. We find evidence that females are less likely to have the opportunity to negotiate over pay. However, conditional on the opportunity to negotiate, they are no less likely to actually negotiate. The analysis does not provide strong evidence that wom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 45 publications
0
14
1
Order By: Relevance
“…This could be due to identity costs generated by social norms or stereotypes that consider “asking” as pushy or “out‐of‐role” behavior by women (Heilman ; Heilman and Okimoto ; Inzlicht ). Results from recent studies suggest however that at least in the modern workplace women are equally likely to ask for promotions and raises (Artz, Goodall, and Oswald ), especially when they face similar opportunities to negotiate relative to their male peers (Stevens and Whelan ). Alternatively, promoted women may strive to adhere to gender norms so as not to “out‐earn” their spouses (Bertrand, Kamenica, and Pan ), or promoted women and their partners may be solving a collective labor‐supply decision that results in women seeking smaller promotions.…”
Section: Resultsmentioning
confidence: 99%
“…This could be due to identity costs generated by social norms or stereotypes that consider “asking” as pushy or “out‐of‐role” behavior by women (Heilman ; Heilman and Okimoto ; Inzlicht ). Results from recent studies suggest however that at least in the modern workplace women are equally likely to ask for promotions and raises (Artz, Goodall, and Oswald ), especially when they face similar opportunities to negotiate relative to their male peers (Stevens and Whelan ). Alternatively, promoted women may strive to adhere to gender norms so as not to “out‐earn” their spouses (Bertrand, Kamenica, and Pan ), or promoted women and their partners may be solving a collective labor‐supply decision that results in women seeking smaller promotions.…”
Section: Resultsmentioning
confidence: 99%
“…Altogether, as women work fewer hours than men given the extant division of labor (Path 2 in Figure 2; BLS, 2018), they may be less likely to initiate negotiations about salary-a relationship visualized as Path 3 in Figure 2 (see also Bowles & McGinn, 2008, which is described in detail below, and Livingston, 2014). As mentioned earlier, Artz et al's (2018) study suggested a positive relationship between weekly hours and the likelihood with which people attempted to get higher pay (for a similar result, see Stevens & Whelan, 2019).…”
Section: The Division Of Labor Has Consequences For the Initiation Ofmentioning
confidence: 70%
“…Women were less likely than men to have attempted to get higher pay in two regressions that included several covariates (Artz et al, 2018). However, this gender difference became non-significant once the number of weekly hours worked was included as an additional covariate (for further analyses on full-time and part-time workers, see Table 4 in Artz et al, 2018; see also Luekemann & Abendroth, 2018;Stevens & Whelan, 2019). As the authors noted (p. 623), "on closer scrutiny, the appearance of a lack of 'asking' is being driven statistically by working fewer hours."…”
Section: The Study By Artz Et Al (2018)mentioning
confidence: 99%
“…Similarly, some have argued that women typically have lower negotiating skills compared to their male counterparts, especially when it comes to asking for promotions and pay raises (Babcock and Laschever ). Recent contributions, though, have failed to find evidence supporting this argument (Artz, Goodall, and Oswald ; Stevens and Whelan ). Women also tend to sort, relatively more than men, into occupations that are more socially rather than monetarily oriented (Grove, Hussey, and Jetter ; Krueger and Schkade ).…”
Section: Introductionmentioning
confidence: 99%